The net neutrality debate on Twitter - Wolf J. Schünemann; Stefan Steiger; Sebastian Stier (Internet Policy Review, 2015)
The internet has been seen as a medium that empowers individual political actors in relation to established political elites and media gatekeepers. The present article discusses this "net empowerment hypothesis" and tests it empirically by analysing Twitter communication on the regulation of net neutrality. We extracted 503.839 tweets containing #NetNeutrality posted between January and March 2015 and analysed central developments and the network structure of the debate. The empirical results show that traditional actors from media and politics still maintain a central role.
Keywords: 300; Net empowerment; Net neutrality; Political participation; Network analysis